1982
DOI: 10.1149/1.2123468
|View full text |Cite
|
Sign up to set email alerts
|

Electron Diffraction Study of the Passive Film on Iron

Abstract: Iron specimens passivated in borate buffer solutions, pH 8.4, have been investigated by transmission electron microscopy. The observed diffraction patterns are characteristic of spinel‐type iron oxide in all specimens independent of the passivation potentials. The orientation relationship between the oxide and iron substrate has been determined to be typical of orientation relationships between fcc and bcc materials,namely, Bain, Kurdjumov‐Sachs, and Nishiyama‐Wasserman types. Specimens have also been examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
2

Year Published

1983
1983
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 16 publications
3
24
0
2
Order By: Relevance
“…Although carbon steel corrosion has been studied extensively , many uncertainties over composition, phase structure, and the film formation and corrosion processes still persist. Early electron diffraction and electrochemical studies [5,25,26] suggest that the passive film formed on iron in borate buffer solutions at pH 8.4 has a spinel, bilayer structure with Fe 3 O 4 at the metal/oxide film interface and ␥-Fe 2 O 3 at the oxide film/solution interface. However, more recent studies, using various in situ surface analyses, suggest a passive film structure ranging from amorphous and similar to Fe hydroxides or oxyhydroxides [14,15,18,20,21,27], to crystalline and consistent with Fe 3 O 4 or ␥-Fe 2 O 3 [28], and even suggest a new crystalline phase with a structure similar to Fe 3 O 4 but with different cation vacancies on octahedral and tetrahedral sites [23].…”
Section: Introductionmentioning
confidence: 99%
“…Although carbon steel corrosion has been studied extensively , many uncertainties over composition, phase structure, and the film formation and corrosion processes still persist. Early electron diffraction and electrochemical studies [5,25,26] suggest that the passive film formed on iron in borate buffer solutions at pH 8.4 has a spinel, bilayer structure with Fe 3 O 4 at the metal/oxide film interface and ␥-Fe 2 O 3 at the oxide film/solution interface. However, more recent studies, using various in situ surface analyses, suggest a passive film structure ranging from amorphous and similar to Fe hydroxides or oxyhydroxides [14,15,18,20,21,27], to crystalline and consistent with Fe 3 O 4 or ␥-Fe 2 O 3 [28], and even suggest a new crystalline phase with a structure similar to Fe 3 O 4 but with different cation vacancies on octahedral and tetrahedral sites [23].…”
Section: Introductionmentioning
confidence: 99%
“…TEM electron diffraction pattern analysis is an ex-situ technique that can be used to determine the structure of oxide films. Using this technique, Foley et al (1967) and Kuroda et al (1982) found that the passive films anodically grown on iron in 0.1 M NaOH solution had a cubic spinel structure, which is structurally very similar to the structures of y-Fe203 and Fe304; but the films were less ordered than the crystalline anhydrous oxides, exhibiting a tendency toward more vitreous structures. Tjong (1985) carried out TEM electron diffraction pattern analysis on the passive film that formed on the iron-chromium alloys in a borate buffer solution (pH 8.4).…”
Section: Tem Studiesmentioning
confidence: 99%
“…Using ex-situ electron diffraction techniques, Foley et al (1967) and Kuroda et al (1982) determined that the anodically grown passive film on iron in acidic solution has a cubic spinel structure, which is structurally very similar to y-Fe203 and Fe304, but the film is less ordered than the crystalline anhydrous oxides, exhibiting a tendency toward more glassy structures. Since film dissolution, film formation, and breakdown all involve the movement of electrons and ions from the metal surface through the passive film, or from the electrolyte into the film, electronic properties of the film are important.…”
Section: Nature and Properties Of Passive Films On Ironmentioning
confidence: 99%
“…No caso específico do ferro e suas ligas, são muitos os estudos utilizando técnicas de análise de superfície combinadas com técnicas eletroquímicas, que tratam da composição, estrutura de fase e processos de formação e crescimento do filme de passivação [3][4][5][6][7].…”
Section: Introductionunclassified
“…Tais estudos mostram que todos estes aspectos dos filmes da passivação do ferro e suas ligas dependem de fatores tais como pH, temperatura e condição redox [3], chegando a ocorrer resultados contraditórios.…”
Section: Introductionunclassified